2016
DOI: 10.5222/buchd.2016.015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the self and the proxy versions of the KIDSCREEN quality of life scale: To what extend can parents predict quality of life of their children?

Abstract: ÖZAmaç: Bu araştırmanın amacı KIDSCREEN sağlıkla ilişkili yaşam kalitesi (SYK) ölçeği öz bildirim yanıt-ları ile vekil yanıtları arasındaki uyumu karşılaştırmaktır. Yöntemler: Araştırma Manisa'da yer alan 6 okulda 8-18 yaş arası 662 çocuk/genç, 543 ebeveyn üzerinde yürütülmüş kesitsel bir araştırmadır. Araştırmada katılımcıların sosyodemografik özellikleri belirlenmiş ve KIDSCREEN yaşam kalitesi anketi uygulanmıştır. Araştırmanın analizinde temel tanımlayıcı bulgular ile öz bildirim-vekil değerlendirmesinin bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…[33] Baydur et al found some inconsistencies in self-report and proxy evaluations in different Turkish versions of KIDSCREEN. [34] The differences between self-report and proxy notifications in our study may be due to cultural adaptation or the difference in perception of stuttering in children and their proxy. Studies addressing consensus or discrepancies between notifications are needed.…”
Section: Discussionmentioning
confidence: 66%
“…[33] Baydur et al found some inconsistencies in self-report and proxy evaluations in different Turkish versions of KIDSCREEN. [34] The differences between self-report and proxy notifications in our study may be due to cultural adaptation or the difference in perception of stuttering in children and their proxy. Studies addressing consensus or discrepancies between notifications are needed.…”
Section: Discussionmentioning
confidence: 66%